Pelatihan Komposting Teknologi Tepat Guna dalam Reduksi Sampah Organik Kampus - Gita Puspa Artiani; Achmad Pahrul Rodji; Sukadi Sukadi; Indriasari Indriasari; Ajat Zatmika; Sutaryo Sutaryo; Reny Savitri; Zefri Zefri; Nazaruddin Khuluk; Rishki Nugraha; Rifqi Maulana; Azka Iqbaal Pratama; Gea Angkasa Irianto Nugroho (Universitas Pahlawan Tuanku Tambusai, 2026)
The accumulation of organic waste in urban areas triggers overcapacity at the Sumur Batu Landfill and causes air pollution due to open burning. This community service activity aims to educate the university community on reducing leaf waste at the source through a composting pilot project at the Faculty of Engineering, Universitas Krisnadwipayana. The methods applied encompass a sociotechnological approach consisting of community education, technical composting training guided by speakers from the North Bekasi District Environmental Health Department (UPTD LH), and the diffusion of science and technology. The starter formulation utilized a mixture of 1 cap of EM4, 1 cap of molasses, and 10 liters of fresh water, followed by an anaerobic fermentation process for 25 days. The results demonstrated a successful collaborative integration of lecturers and students across multiple departments (Civil Engineering, Mechanical Engineering, Architecture, and Urban and Regional Planning) in producing ready-to-use organic fertilizer applied to the campus's productive trees. In conclusion, managing waste independently from its source is crucial as a tactical solution to reduce regional ecological burdens while creating a clean, healthy, and sustainable campus ecosystem.